Penggunaan Media KIT IPA untuk Meningkatkan Kemampuan Siswa dalam Memahami Materi Gaya Magnet - Ngadinem Ngadinem (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This class action research has a background problem that is the low learning outcomes of science students in grade V SD Negeri 5 Kedungringin 2014/2015 school year. This study aims to improve student learning outcomes in science subjects, especially about magnetic forces and to improve the professionalism of teachers as educators. The research was carried out through the use of the Natural Science KIT and demonstration model learning and carried out in two stages, namely through cycle I and cycle II. After the implementation of this research, it is known that student learning outcomes in science learning about magnetic force is increasing. This is evidenced by the results of science learning obtained in pre-cycle that 36% of students have been completed. After being given an action it has increased to 68% and in the second cycle to 100%. The conclusion of this research is that using the Natural Science KIT and demonstration model learning can improve the learning outcomes of Natural Sciences in fifth grade students especially about magnetic forces.